Inventarisasi Tumbuhan Famili Fabaceae di Jalur Hutan Kota Babakan Siliwangi Bandung, Jawa Barat - Futri Assyifa; Habib Indraswara; Ateng Supriatna (Konstanta : Jurnal Matematika dan Ilmu Pengetahuan Alam, 2023)
Plants are a group of living things that have many cells on earth. Plants have three parts, namely roots, stems and leaves. Babakan Siliwangi has been designated as the lungs of the city and a recreational area in Bandung by Unesco. Having an area of ​​3.8 hectares filled with various animals that complement the ecosystem, Babakan siliwangi has become a Green Open Space (RTH) that can be reached by the people of Bandung City. The Fabaceae family is one of the third largest families which belongs to the members of closed seed plants (Angiosperms) which are easily found in the surrounding environment which have a variety of morphology or stature ranging from herbs, seedlings, shrubs and trees.